2013
DOI: 10.1097/scs.0b013e31827c83ea
|View full text |Cite
|
Sign up to set email alerts
|

Co-Occurrence and Possible Role of Sinonasal Anomalies in Primary Acquired Nasolacrimal Duct Obstruction

Abstract: Although primary acquired NLD obstruction seems to be an ophthalmologic problem, rhinologic problems have great importance in etiology. Detailed endoscopic examination and preoperative paranasal sinus computed tomography will reveal the possible role of nasal and paranasal structures adjacent to lacrimal sac in etiology of NLD obstruction. This will be effective both on conservative treatment and postoperative success in patients scheduled for surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 9 publications
1
10
2
Order By: Relevance
“…[21] In a recent study performed in Turkey by Habesoglu et al, the authors examined sinonasal anomalies which accompanied nasolacrimal duct obstruction in 41 patients and they found statistically significant rates for concha bullosa, inferior concha hypertrophy, osteomeatal com- plex disease and maxillary sinusitis, while the rates of nasal septum deviation, middle concha disorders, presence of Onodi and agger nasi cells were not statistically significant in these 14 patients. [22] As an outcome of the present study, even though we found higher rates of lateral wall and sinus pathologies in patients with distal LDO, we have concluded that these manifestations failed to clarify the etiology of the disease and just like functional endoscopic sinus surgery, computed-tomographic imaging techniques will have an gradually increasing importance in the evaluation of the patients with LDO.…”
Section: Discussioncontrasting
confidence: 45%
“…[21] In a recent study performed in Turkey by Habesoglu et al, the authors examined sinonasal anomalies which accompanied nasolacrimal duct obstruction in 41 patients and they found statistically significant rates for concha bullosa, inferior concha hypertrophy, osteomeatal com- plex disease and maxillary sinusitis, while the rates of nasal septum deviation, middle concha disorders, presence of Onodi and agger nasi cells were not statistically significant in these 14 patients. [22] As an outcome of the present study, even though we found higher rates of lateral wall and sinus pathologies in patients with distal LDO, we have concluded that these manifestations failed to clarify the etiology of the disease and just like functional endoscopic sinus surgery, computed-tomographic imaging techniques will have an gradually increasing importance in the evaluation of the patients with LDO.…”
Section: Discussioncontrasting
confidence: 45%
“…Habesoglu et al (9) found concha bullosa, inferior concha hypertrophy, osteomeatal disease and maxillary sinusitis, but not nasal septal deviation, middle concha disorders and ethmoid sinusitis, to be significant in this patient group. In contrast, there are studies reporting that NDO is not associated with nasal pathologies.…”
Section: Discussionmentioning
confidence: 55%
“…Kallman et al 6 reported sino-nasal anomalies (osteomeatal complex disease, ethmoidal opacification, agger nasi cell opacification, concha bullosa, and nasal septal deviation) in 87% of patients with NLD obstruction versus 63% of the control group ( p < 0.05) on coronal CT-PNS. Habesgolu et al 9 reported significantly higher numbers of concha bullosa, inferior turbinate hypertrophy and osteomeatal disease on the side of NLD obstruction versus contralateral side ( p < 0.05) on CT-PNS. However, in their study, nasal septal deviation, ethmoidal sinusitis and irregularity of middle turbinate were no different on either sides.…”
Section: Discussionmentioning
confidence: 95%
“…Apart from nasal septum, no other intranasal features were documented in these studies. Computed tomography based data exists on associated sino-nasal anomalies in PANDO 6, 7, 8, 9, 10, 11, 12. Similar significant endoscopic intranasal anomalies and pathologies have been described to be associated with congenital nasolacrimal duct obstruction 13 .…”
Section: Introductionmentioning
confidence: 87%